Point-of-Care B-Type Natriuretic Peptide and Neutrophil Gelatinase-Associated Lipocalin Measurements for Acute Resuscitation. Issue 2 (March 2015) - Howell, Erin; Sen, Soman; Palmieri, Tina; Godwin, Zack; Bockhold, Jennifer; Greenhalgh, David; Tran, Nam K.
<x xml:space="preserve">Abstract</x> Adequate resuscitation is paramount to burn patient survival and recovery. Novel biomarkers of intravascular volume and renal perfusion may augment resuscitation strategies. The purpose of this study is to characterize serum B-type natriuretic peptide (BNP) and neutrophil gelatinase-associated lipocalin (NGAL) during burn resuscitation and correlate to clinical assessments of volume status. We hypothesize that BNP and NGAL will help predict inadequate resuscitation during the first 48 hours following burn injury. We conducted a pilot observational study recruiting 15 adult (age ≥18 years) patients with ≥20% TBSA burns. Paired serial BNP, NGAL, and creatinine measurements were performed using point-of-care testing. Samples were tested every 4 hours for the first 48 hours following admission. Acute kidney injury (AKI) was defined by the RIFLE criteria. Over-resuscitation was defined as developing compartment syndrome. Demographics and TBSA were similar between AKI (n = 7) vs non-AKI (n = 8), and over-resuscitated (n = 5) vs adequately resuscitated groups (n = 10). NGAL (184.9 ± 72.2 vs 110.8 ± 35.8 ng/ml, P = .004) and BNP (25.3 ± 17.3 vs 8.8 ± 5.2 pg/ml, P = .033) values were significantly higher in AKI patients. Creatinine values were similar between AKI and non-AKI patients. NGAL levels suggested presence of AKI 12 hours earlier than creatinine levels. BNP values (23.1 ± 21.9 vs 13.9 ± 13.4 pg/ml, P < .001) were significantly higher in over-resuscitated patients. Point-of-care BNP, NGAL, and creatinine measurements aid in the assessment of vascular volume and renal function during acute burn resuscitation. Further studies are warranted to determine BNP and NGAL cut-offs for guiding burn resuscitation.